2009
DOI: 10.1158/1940-6207.capr-08-0192
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sulforaphane-Rich Broccoli Sprouts Reduce Colonization and Attenuate Gastritis inHelicobacter pylori–Infected Mice and Humans

Abstract: The isothiocyanate sulforaphane [SF; 1-isothiocyanato-4(R)-methylsulfinylbutane] is abundant in broccoli sprouts in the form of its glucosinolate precursor (glucoraphanin). SF is powerfully bactericidal against Helicobacter pylori infections, which are strongly associated with the worldwide pandemic of gastric cancer. Oral treatment with SF-rich broccoli sprouts of C57BL/6 female mice infected with H. pylori Sydney strain 1 and maintained on a high-salt (7.5% NaCl) diet reduced gastric bacterial colonization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(190 citation statements)
references
References 36 publications
7
179
2
2
Order By: Relevance
“…Capsaicin has an anti-inflammatory effect and inhibited H. pylori-induced interleukin (IL)-8 production by gastric epithelial cells [160] . Sulphoraphane has also been indicated to suppress colonization and inhibit gastritis in H. pylori-infected mice and humans [161] .…”
Section: Eradication: Hope Is Coming?mentioning
confidence: 99%
“…Capsaicin has an anti-inflammatory effect and inhibited H. pylori-induced interleukin (IL)-8 production by gastric epithelial cells [160] . Sulphoraphane has also been indicated to suppress colonization and inhibit gastritis in H. pylori-infected mice and humans [161] .…”
Section: Eradication: Hope Is Coming?mentioning
confidence: 99%
“…As shown here, treatment with B. oleracea extract decreased the severity of esophagitis without genotoxic and cytotoxic effects. The principal compound present in B. oleracea capable of attenuating inflammation is SF, as demonstrated in gastritis and skin inflammation studies (22)(23)(24)(25). These studies have shown that SF suppresses proinflammatory cytokines, such as tumor necrosis factor-α, interleukin-1β and interleukin-6 via nuclear factorerythroid-2-related factor and/or inhibition of the activator protein-1.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, the present study is the first to describe the anti-inflammatory effect of a B. oleracea extract in esophageal tissue. Of particular interest was the finding that the anti-inflammatory effect was observed at a much lower oral dose of SF/day compared to the doses used in a variety of other rodent experiments (22,23,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Although they are regarded as a healthy food from a nutritional standpoint [1,2], seed sprouts (alfalfa, broccoli, radish, mung bean, etc.) have historically been problematic from a food safety perspective, as they have been associated with several multistate and international outbreaks of bacterial disease over the past decade or longer [3,4].…”
Section: Introductionmentioning
confidence: 99%